UV inactivation of humic-coated bacteriophages MS2 and T4 in water. Issue 6 (1st November 2006) - Hofmann, R; Andrews, R C; Templeton, M R
Abstract : This bench-scale study investigated the hypothesis that humic acids may thinly coat the surfaces of viruses (bacteriophages MS2 and T4) and thereby protect them from inactivation by UV light (254 nm). The model viruses were mixed in buffered water (pH 5.5) that contained Aldrich ® humic acid (AHA) concentrations of 0, 10, 50, and 150 mg/L and were exposed to UV light at 40 and 80 mJ/cm 2 for bacteriophage MS2 and 2 and 7 mJ/cm 2 for bacteriophage T4 using a low pressure UV collimated beam. No steps were taken to form particles (i.e., no coagulant was added). The UV inactivation of both bacteriophages decreased to a statistically significant degree (based on 95% confidence level, Student's t test) at a humic acid concentration of 150 mg/L at the higher UV doses for each phage. This was despite the increased UV absorbance at 254 nm (UV254 ) caused by the humic acid being taken into account in the UV dose calculation. It was therefore hypothesized that the humic acid was coating the phage surfaces with a thin UV-shielding layer. As a further investigation of this hypothesis, samples containing humic acid, both with and without phage, were pelletized by ultracentrifugation and re-suspended in pure Milli-Q ® water and the resulting UV254 values were compared. It was anticipated that the re-suspended pellets from the solutions containing humic acid and phage would exhibit higher UV254 than those of the pellets from solutions containing either phage or humic acid, due to the coating interaction. While there were statistically significant differences in UV254 among some of the re-suspended pellets, the results were inconsistent due to limitations of the experiment. As such, while some supporting evidence for the humic coating hypothesis was provided by this initial proof of concept study, further research is needed to more fully understand this phenomenon.